CHANGES IN CARDIOMYOCYTE NUCLEI LOCATION AND CONFORMATION DURING POSTNATAL DEVELOPMENT OF WISTAR RATS - Zagoruyko, G.E.; Martsynovskyi, V.P.; Filatova, V.L.; Matvienko, T.M.; Sargosh, O.D.; Gusakovska, T.M. (World of Medicine and Biology, 2024)
The study examines the characteristics of changes in the location and causes of deformation of cardiomyocyte nuclei in the left ventricle of Wistar rats. The analysis was conducted on a series of electron microscopic images of rat myocardium from birth to 45 days of postnatal development. The study identified four zones of nucleus location in cardiomyocytes: central, marginal, under the sarcolemma, and in the sarcolemma protrusion into the interstitial space. The location of the nucleus was most frequently determined in the marginal zone, which is biologically appropriate as it reduces the distance for chemical transport from blood capillaries to the sarcoplasm and nucleus. Occasionally, under normal conditions of rat myocardial functioning, protrusion of the nucleus and sarcolemma into the interstitium is observed, which does not affect the contractile function of the cardiomyocyte. The nucleus located in the protrusion of the sarcolemma is inactive state. When metabolic processes intensify, the nucleus moves from the sarcolemmal protrusion into the “body” of the cardiomyocyte, where its functional properties become activated. During the 'contraction ↔ relaxation' process of cardiomyocytes, short-term impulse pressures from myofibrils and mitochondria cause deformation and reorganization of the 3D genome of the nucleus, which may lead to changes in gene expression.
Keywords: cardiomyocyte; nucleus; conformation; localization; apoptosis